Circulating IGF-binding protein 7 (IGFBP7) levels are elevated in patients with endometriosis or undergoing diabetic hemodialysis - Sasajima Koji; Matsuda Akihisa; Matsutani Takeshi; Higuma Chinatsu; Itokazu Osamu; Isaka Keiichi; Momose Katsutoshi; Ishihara Ryosuke; Kutsukake Masahiko; Hara Takahiko; Tamura Kazuhiro (BMC, 2008)
Abstract Background Insulin-like growth factor-binding protein-7 (IGFBP7) is a secretory protein with a molecular mass of approximately 30 kDa. It is abundantly expressed in the uterine endometrium during the secretory phase of the menstrual cycle. Decreased IGFBP7 expression has been observed in some cancers and leiomyomata. Methods To determine whether serum IGFBP7 levels reflect changes in uterine IGFBP7 expression in humans during the menstrual cycle, and to examine whether serum IGFBP7 levels are altered in patients with various disorders, we developed a novel, dual-antibody sandwich enzyme-linked immunosorbent assay (ELISA). Firstly, concentrations of IGFBP7 released into the medium were determined in cultured endometrial stromal and glandular cells. Blood samples were collected from women who had normal menstrual cycles and who had been diagnosed with endometriosis. Serum from hemodialysis patients and gastrointestinal cancers was also used to determine the IGFBP7 levels. Results Using this new ELISA, we demonstrated that cultured uterine cells secrete IGFBP7 into the medium. Patients with endometriosis and those with type II diabetes mellitus undergoing hemodialysis had significantly higher serum concentrations of IGFBP7 than the relevant control subjects. There were no differences in serum IGFBP7 levels in women at different stages of the menstrual cycle. Furthermore, serum IGFBP7 levels in patients with colorectal, esophageal, or endometrial cancer were not different than normal healthy subjects. Conclusion Our observations suggest that IGFBP7 is associated with the pathophysiology of endometriosis and diabetes mellitus, and that serum IGFBP7 levels do not reflect enhanced uterine expression of IGFBP7 mRNA during the menstrual cycle.